Intimidating calls. Are we facing a crime of scam or extortion? - Guillén Ledesma, María Eugenia (2016)
There are criminal behaviors that are difficult to describe. One of those are the so called «intimidating calls» where a person acts like the informant to report a fake situation like a kidnapping, or a police custody of a relative, in order to frighten the victim so the criminal can obtain a large amount of money out of this situations. The delinquent deceives and frightens the victim, making it easy for this malefactor to manipulate him or her. The victim ends up been traumatized by this episode and loosing his/her money after realizing that is part of a ruse. The bottom line is how to define precisely this criminal event. Some call it «scam» (fraud) and others refer to it as «extortion» (a variety of blackmail). The main difference is that on the first case there is no intimidation against the victim or threat. Whereas on the second case this two elements are present. The main purpose of this article is to point out this topic and to explain that in fact there is a difference between this two terms «scam» and «extortion» when it comes to describe this type of crime known as «intimidating calls». This explanation should be useful to identify them correctly and give a fair judgment.